PENINGKATKAN KESADARAN SISWA-SISWI SMKN 05 KENDARI MELALUI EDUKASI INTERAKTIF MENGENAI IDENTIFIKASI DAN PEMILIHAN KOSMETIK YANG AMAN DAN LEGAL - Muliadi, Rahmat; Leorita, Mesi; Tias, Ayuning; Sarry, Elita Puspita; Rosmaria, Rosmaria; Hartawaty, Siska Septy; Septrilia, Shara; Aspadiah, Vica; Malik, Fadhliyah; Indalifiany, Astrid (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Educating young people about product safety is becoming increasingly important as the cosmetics industry evolves rapidly. A community outreach program was held at SMKN 05 Kendari in Southeast Sulawesi to enhance teenagers’ awareness of selecting safe and legally approved cosmetic products. The program utilized an engaging educational format, including presentations, group discussions, and interactive Q&A sessions, supported by PowerPoint slides. Key topics included identifying the differences between legal and illegal cosmetics, understanding the dangers of harmful substances in beauty products, and learning how to verify products using the BPOM KLIK platform. The outcome showed a noticeable improvement in participants' knowledge regarding the selection of safe cosmetics. This initiative is expected to encourage more informed consumer choices and help reduce the use of illegal cosmetics among teenagers